Ferritin1-mediated ferroptosis participates in granular acini degeneration of Haemaphysalis longicornis salivary glands - Dongqi Yuan; Songqin Chen; Yongzhi Zhou; Jie Cao; Houshuang Zhang; Yanan Wang; Jinlin Zhou (Ticks and Tick-Borne Diseases)
Ticks (Haemaphysalis longicornis) transmit pathogens to their hosts through their salivary glands during blood-feeding. The salivary glands of adult parthenogenetic H. longicornis undergo degeneration post-engorgement. Clarifying the molecular mechanisms underlying salivary gland degeneration of H. longicornis is conducive to identifying novel targets for preventing and controlling these widespread vectors. In this study, we investigated the salivary glands of adult parthenogenetic H. longicornis to elucidate the relationship between ferroptosis, iron-dependent cell death, H. longicornis ferritin 1 (HlFer1) and salivary gland degeneration post-attachment and post-engorgement. Fluorescence microscopy, revealed increased iron accumulation, reactive oxygen species, lipid peroxidation, and decreased mitochondrial cristae in the granular acini of H. longicornis salivary glands post-engorgement. The results of a qPCR analysis indicated that HlFer1, glutathione peroxidase 4 (GPX4), transferrin (TRF), and high mobility group protein B1 (HMGB1) expression elevated in H. longicornis salivary glands post-attachment and post-engorgement. In vitro culture of H. longicornis salivary glands showed that erastin promotes ferroptosis, while ferrostatin-1 blocks this process. RNA interference (RNAi) targeting HlFer1 promoted ferroptosis in salivary gland granular acini. In conclusion, we demonstrated that HlFer1-induced ferroptosis is a key molecular mechanism underlying the salivary gland granular acini degeneration of H. longicornis. Our findings are important for developing novel preventive measures against H. longicornis as a disease vector.